2011
DOI: 10.1121/1.3533692
|View full text |Cite
|
Sign up to set email alerts
|

Effects of poroelastic coefficients on normal vibration modes in vocal-fold tissues

Abstract: The vocal-fold tissue is treated as a transversally isotropic fluid-saturated porous material. Effects of poroelastic coefficients on eigenfrequencies and eigenmodes of the vocal-fold vibration are investigated using the Ritz method. The study demonstrates that the often-used elastic model is only a particular case of the poroelastic model with an infinite fluid-solid mass coupling parameter. The elastic model may be considered appropriate for the vocal-fold tissue when the absolute value of the fluid-solid ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…A study of the pore architecture of bovine acellular VF tissue showed that structural anisotropy is not significant, and moreover, the medial–lateral permeability (as considered in the present study) is high enough to allow interstitial fluid flow . In an approach similar to ours, interstitial fluid flow in the anterior–posterior direction was assumed negligible by other workers based on the following two observations: (i) the stress gradients in that direction are low even when the VF is intrinsically transversely isotropic and (ii) water flow is dominated by negatively charged non‐fibrillar matrix molecules, which are usually distributed isotropically in the VF tissue. From the earlier arguments, isotropic permeability as considered here appears to be a reasonable assumption.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…A study of the pore architecture of bovine acellular VF tissue showed that structural anisotropy is not significant, and moreover, the medial–lateral permeability (as considered in the present study) is high enough to allow interstitial fluid flow . In an approach similar to ours, interstitial fluid flow in the anterior–posterior direction was assumed negligible by other workers based on the following two observations: (i) the stress gradients in that direction are low even when the VF is intrinsically transversely isotropic and (ii) water flow is dominated by negatively charged non‐fibrillar matrix molecules, which are usually distributed isotropically in the VF tissue. From the earlier arguments, isotropic permeability as considered here appears to be a reasonable assumption.…”
Section: Discussionmentioning
confidence: 53%
“…Time-dependent responses such as creep and stress relaxation are equivalent to macroscale viscoelastic behavior [12,13]. Biphasic material analysis has been carried out for VF tissue [14][15][16][17][18][19] as well as for other biological tissues (e.g., bone [20]). Computations performed in [2] indicated that VF vibration-induced systemic hydration could be significant.…”
Section: Introductionmentioning
confidence: 99%
“…The poroelastic theory has also been used to describe the viscoelastic behavior of vocal fold tissue, 16 the liquid redistribution in the vocal folds during phonation, 17,18 and the normal model of the vocal folds vibration. 19 Recently, Bhattacharya and Siegmund 20,21 developed a high-fidelity numerical model, taking into account the tissue viscoelastic properties derived from biphasic theory. By estimating fluid movement from the hydrostatic stress gradient, they revealed that vibration and collision of the vocal folds will change the state of hydration within the tissue.…”
Section: Introductionmentioning
confidence: 99%
“…The poroelastic theory describes the dynamic behavior of the fluid component of vocal tissue and its interaction with the solid matrix. In comparison to the previous models, which did not consider the vocal fold contact, 18,19 ignored the solid-fluid interaction stress from the solid equations, 20,21 or imposed a time varying air pressure instead of a self-oscillating model, 23 this current model accounts for liquid-solid interaction, liquid movement, vocal fold contact, air pressure distribution obeying Bernoulli's law, and the flow-induced vocal fold self-vibration. Therefore, this model allows us to investigate the liquid movement in three directions and explores the effect of vocal fold contact on the liquid dynamics in vibrating vocal folds.…”
Section: Introductionmentioning
confidence: 99%
“…This modification introduces a 7 × 7 elastic stiffness tensor C ij as an extension to the typical 6 × 6 stiffness tensor. The new tensor elements, poroelastic constants, are used to derive the effective elastic moduli and hence to describe the elasticity of porous materials . Biot's theory implies that the elasticity of the porous material primarily depends on the porosity and the pressure of the pore‐saturated fluid.…”
Section: Introductionmentioning
confidence: 99%